Rosen's emergency medicine concepts and clinical practice - Rosen, Peter, 1935-; Marx, John A. (Elsevier/Saunders, 2014)
In an emergency, you only have one chance... and usually very little time... to make the right decision. How can you be certain you have the knowledge you need? This title places the advanced knowledge in emergency medicine at your fingertips.